Genre analysis of the introduction and literature review sections in hospitality management research articles - De Mello, Geraldine (2011)
This study examined the rhetorical structure of the introduction and literature review sections of the Hospitality and Management research articles and determined the similarities and differences in the two sections. The study also identified the selected linguistic choices used in both the sections. It investigated the moves analysis for principal moves and steps in the introduction and literature review sections and also focuses on how the individual moves and constituent steps are realized by linguistic choices. The samples comprised 20 introductions and 20 literature review sections from the Hospitality and Management journal. The study used the genre analysis approach to analyse the moves. Swales revised CARS Model (2004) was used to analyse the moves. The findings revealed that the Introductions and literature review sections in Hospitality and Management journal articles used the same move pattern, but are different in their use of steps. The introduction sections analyzed showed that Move 1, 2 and 3 are obligatory moves and Hospitality and Management research article writers must include them in their introduction sections. The literature review sections display cyclical move patterns that show the presence of the 3 moves and their respective steps postulated in Swales 2004 revised CARS model. The lexico-grammatical information obtained particularly the use of demonstrative pronouns such as ‘these’ and those are often used in both theintroduction and literature review sections and the use of hedging devices are rarely used. These findings have valuable implications as these results not only contribute to learners’ understanding to the nature of the introduction genre, but also serve as reliable sources that can be used to incorporate into teaching materials. The pedagogical implication of this study is that the results obtained may assist teachers in designing instructional materials that support the acquisition of generic skills among hospitality and management students. More importantly, the moves identified in the introduction and LR sections of the Hospitality and Management research articles would be of great help to the hospitality students in writing introductions and literature review for journal articles. The linguistic features such as the use of modals , conjuncts, hedging, sub-headings and citations may be presented as a phrase bank which can be effectively used as a guide to achieve a wide range of communicative intentions.